Sustainable Development Strategies of Rainfed Paddy Fields in Central Java, Indonesia: A Review - Nourma Al Viandari; Anicetus Wihardjaka; Heru Bagus Pulunggono; Suwardi Suwardi (Caraka Tani: Journal of Sustainable Agriculture, 2022)
Rainfed paddy fields have a great potential to be developed in Indonesia, especially in Central Java. However, water irrigation management, drought stress, pest and disease infestation and low nutrients that affect paddy yield remain the constraints. Unpredictable climate pattern is also a limiting factor in the cultivation of rainfed paddy fields. This narrative review aims to identify and discuss solutions to problems that exist to increase the yield of rainfed paddy fields with several techniques that support sustainable agriculture. This review paper was prepared by collecting government data and interviews with several farmer group leaders as complementary data. Based on field conditions, farmers in rainfed paddy fields provide fertilization inputs that are not following the fertilizer recommendations. Moreover, field conditions with limited water availability have caused paddy cultivating in several locations only once a year with low yields. Water storage can help farmers meet the need for water, especially during dry and water-stress conditions. The farmers also need to pay attention to the appropriate fertilization doses and the use of additional organic matter derived from cultivation residues, which are expected to increase the availability of nutrients in the soil. The use of short-life and drought-resistant varieties can aid in overcoming the problem of crop failure in the middle phase caused by water scarcity. Finally, we identify and emphasize that rainfed paddy fields generally have a limiting factor for water and nutrients and several technologies are needed to contribute to increasing more sustainable paddy yields.